Simple Harmonic Oscillator Model of O2 Molecule in Vacuum: A Classical Molecular Dynamics Study - Salmahaminati, Salmahaminati (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2018)
The simple harmonic oscillator model allows a basic understanding of all processes and can be used to analyse optical vibrational modes and electronic transitions in atoms, molecules and crystals, in order to derive general properties of harmonic generation to all orders. In particular, we are done to investigate single, ten, and twenty harmonic oscillator of O2 molecule using GROMACS 4.55. Time is the important factor in simulation because the best result of simulation can be obtained by increasing the number of steps and by decreasing the timesteps. Since the properties only depend on time and not on the specific microscopic model, they can also be adopted for the quantum-mechanical description by using in the classical molecular dynamics.Â